Enabling A Competitive Mobile Sector in Emerging Markets Through the Development of Tower Companies - Houngbonon, Georges Vivien; Rossotto, Carlo Maria; Strusani, Davide (International Finance Corporation, Washington, D.C., 2021)
Sharing mobile network infrastructure through specialized companies called towercos is a business model with the potential to accelerate access to quality mobile connectivity for individuals and businesses in emerging markets. A significant number of developing countries have yet to adopt this model, however, and many others continue to struggle with competition issues within their tower markets. This note provides the rationale and policy options for a light regulatory regime that can enable the entry and sustainable development of a dynamic market for towercos in emerging markets. The note also discusses the evolution of the towerco model into small cells and distributed antenna systems, both of which help enable high-speed mobile connectivity technologies like 4G and 5G.